Simulation-Based Medical Education and Training Enhance Anesthesia Residents' Proficiency in Erector Spinae Plane Block - Torrano, Vito; Zadek, Francesco; Bugada, Dario; Cappelleri, Gianluca; Russo, Gianluca; Tinti, Giulia; Giorgi, Antonio; Langer, Thomas; Fumagalli, Roberto (Frontiers in Medicine, 2022)
Background: Advances in regional anesthesia and pain management led to the advent of ultrasound-guided fascial plane blocks, which represent a new and promising route for the administration of local anesthetics. Both practical and theoretical knowledge of locoregional anesthesia are therefore becoming fundamental, requiring specific training programs for residents. Simulation-based medical education and training (SBET) has been recently applied to ultrasound-guided regional anesthesia (UGRA) with remarkable results. With this in mind, the anesthesia and intensive care residency program of the University of Milano-Bicocca organized a 4-hours regional anesthesia training workshop with the BlockSim® (Accurate Srl, Cesena) simulator. Our study aimed to measure the residents’ improvement in terms of reduction in time required to achieve an erector spinae plane (ESP) block. Methods: Fifty-two first-year anesthesia residents were exposed to a 4-hours training workshop focused on peripheral blocks. The course included an introductory theoretical session held by a locoregional anesthetist expert, a practical training on human models and mannequins using Onvision® (B. Braun, Milano) technologies, and 2 test performances on the BlockSim simulator. Residents were asked to perform 2 ESP blocks on the BlockSim: the first without previous practice on the simulator, the second at the end of the course. Trainees were also also asked to complete a self-assessment questionnaire. Results: The time needed to achieve the block during the second attempt was significantly shorter (131 [83, 198] vs. 68 [27, 91] seconds, p <0.001). We also observed a reduction in the number of needle insertions from 3 [2, 7] to 2 [1, 4] (p=0.002), and an improvement aiming correctly at the ESP from 30 (58%) to 46 (88%) (p <0.001). Forty-nine (94%) of the residents reported to have improved their regional anesthesia knowledge, 38 (73%) perceived an improvement in their technical skills and 46 (88%) of the trainees declared to be “satisfied/very satisfied” with the course. Conclusions: A 4-hour hands-on course based on SBET may enhance first-year residents' UGRA ability, decrease the number of punctures and time needed to perform the ESP block, and improve the correct aim of the fascia.